BeeFunc, a comprehensive trait database for French bees - Lucas Aubouin; David Genoud; Bérénice Givord-Coupeau; Sandrine Tercerie; Olivier Gargominy; Benoît Geslin; Bertrand Schatz (Scientific Data)
Abstract Given pollinator’s reported decline, it is of utmost importance to better understand the vulnerability of wild bees to human pressures. One way to achieve this goal is to explore how their traits are associated with exposure to anthropogenic perturbations. To date, there is no database synthesizing traits of bees at the species level in France, limiting the functional interpretation of inventories. We present BeeFunc 1.0, the first database on traits for the entire fauna of French wild bees. Based on extensive literature research and expert knowledge, the database is structured according to the French taxonomic register (TAXREF) and its associated knowledge base. The base gathers 26,176 trait information from 483 sources, describing 932 species for 20 features related to morphology, ecology, biogeography, and conservation. BeeFunc is intended to be collaborative and regularly updated. Bees can finally be better considered from a functional perspective. We expect this database to be widely used by researchers, conservationists, naturalists, and stakeholders, stimulating future research on wild bees.